ANTIOXIDANT ACTIVITY OF HERBAL YOGHURT INCORPORATED WITH CINNAMON (CINNAMOMUM ZEYLANICUM) EXTRACT - C.B. Manju; K. Radha; Binsy Mathew; Jamuna Valsalan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The aim of the study was to develop herbal yoghurt by incorporating cinnamon bark extract (Cinnamomum zeylanicum) at 0.6 and 1.2 per cent level. The developed herbal yoghurt samples were analysed for physico-chemical properties, antioxidant activity and sensory quality by standard procedures. The incorporation of cinnamon extract improved the antioxidant activity of yoghurt significantly. The antioxidant activity of control and cinnamon incorporated yoghurt (0.6 and 1.2 per cent) were 28. 12±2. 16, 44.87+2.16 and 54.77±2.16 per cent, respectively. A decline in antioxidant activity was observed in all yoghurt samples after the third day of storage. No significant difference in fat and total solids content was observed in yoghurt samples incorporated with cinnamon extract. The sensory scores of yoghurt incorporated with 0.6 per cent cinnamon extract were significantly higher than that of control. The study revealed that cinnamon extract can be incorporated into yoghurt to enhance the antioxidant activity without compromising the sensory quality.